Screening of Novel 1,2,4-triazine Clubbed 1,2,3-triazole Derivatives as α-glucosidase Inhibitors: In Silico Study - Chaturvedi, Neha; Bhattacharya, Sushanta; Asati, Vivek; Chtita, Samir; Kaya, Savaş; Almehizia, Abdulrahman A.; Dubey, Raghvendra (Letters in Drug Design & Discovery, 2024)
IntroductionA new set of 1,2,4-triazine combined 1, 2, 3-triazole hybrids were designed computationally for predicting anti-diabetic potential. All the derivatives taken for study exhibited excellent anti-diabetic potential with significant IC50 values.MethodsThe present research includes the development of pharmacophore models, 3D QSAR, virtual screening, molecular docking, and evaluation of models based on certain criteria. The DHRRR_1 showed the best pharmacophore model with a survival score of 5.9937. The 3D QSAR analysis developed a model with the values of R2 = 0.9714 and Q2 = 0.7202. The binding pose and affinity of the most potent compound, 10c, in the active site of α-glucosidase was investigated using in-silico molecular docking analysis.ResultsIt was observed that compound 10c demonstrated promising binding affinity with a score of -8.078 kcal/mol and exhibited binding interaction with the essential amino acids ASN301 and LEU227. There were five compounds (1-5) that showed significant binding affinity towards the target comprising active amino acids (ASH202, ASP333 and VAL335). The molecular dynamic study showed the stability of ligand-protein binding interactions.ConclusionThe results of the present investigation can accelerate the optimization and reformation of the latest anti-diabetic agents that target the α-glucosidase.
Keywords: triazole